Michelangelo - the Last Judgment a glorious restoration - Partridge, Loren W.; Colalucci, Gianluigi; Mancinelli, Fabrizio (New York Harry N. Abrams, 1997)
Francesco Buranelli; Loren Partridge; Fabrizio Mancinelli; Gianluigi Colalucci
Simultaneously published in Italian
Includes bibliographical references (p. 205-206)
Keywords: Michelangelo Buonarroti -- 1475-1564; Michelangelo Buonarroti -- 1475-1564 -- Criticism and interpretation; Judgment Day in art; Mural painting and decoration, Italian -- Conservation and restoration -- Vatican City; Mural painting and decoration, Renaissance -- Conservation and restoration -- Vatican City; Cappella Sistina (Vatican Palace, Vatican City); Tòa thánh Vatican; Hội họa